2022
DOI: 10.3389/fnagi.2022.845105
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and Anxiety Outcomes Related to Visiting Policy Changes in the Intensive Care Unit During the COVID-19 Pandemic

Abstract: ObjectiveTo evaluate the effect of intensive care unit (ICU) visit on the incidence of delirium, delirium subtype, and anxiety level in ICU patients.MethodsTrained psychiatrists and nurses evaluated ICU patients for delirium, delirium subtypes, and anxiety. Propensity score matching (PSM) was used to retrospectively analyze the data. Then, we compared the differences in the incidence of delirium, delirium subtypes, and anxiety level before and after the ICU visit ban. Logistic regression was conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
7
0
4
Order By: Relevance
“…While the causal association between the patient-family separation and adverse psychological outcomes of the caregivers needs further investigation, a study conducted in Turkey with 120 ICU family caregivers reported visitation restriction as an independent risk factor for worse depressive symptoms in caregivers [31] . In South Korea, the effects of visitation restrictions on the outcomes of patients or families have not yet been investigated fully, except for one study that reported visitation restriction as a risk factor for the non-hypoactive delirium subtype and worse anxiety symptoms in patients [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the causal association between the patient-family separation and adverse psychological outcomes of the caregivers needs further investigation, a study conducted in Turkey with 120 ICU family caregivers reported visitation restriction as an independent risk factor for worse depressive symptoms in caregivers [31] . In South Korea, the effects of visitation restrictions on the outcomes of patients or families have not yet been investigated fully, except for one study that reported visitation restriction as a risk factor for the non-hypoactive delirium subtype and worse anxiety symptoms in patients [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Since February 2020, family visitation has been completely banned in most ICUs in South Korea, including our institution. While studies have examined how current family engagement efforts has been changed since COVID-19 pandemic [12] and effects of visitation restriction on delirium and anxiety among the ICU patients [13] , little is known about the quality of life, emotions, and perceptions toward the visitation policies among ICU family caregivers since the start of the COVID-19 pandemic in South Korea. In South Korea, flexible and open visitation was not a norm in ICU settings, which was different from other countries where family visits were more flexible and for longer durations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that 30% to 51.8% of critically ill COVID-19 patients had at least one episode of hyperactive delirium, which is substantially higher than the pre-pandemic incidence of 12.7% in critically ill patients [50,54,55]. The reason behind this high rate of agitation in COVID-19 patients is unclear; this could be related to the greater severity of COVID-19 lung injury and higher levels of ventilatory support, the frequent use of prone positioning, a relatively higher incidence of young individuals needing critical care during early COVID-19 surges, crisis staffing with providers less experienced in effective sedation management, decreased family visitation, or perhaps biological mechanisms unique to SARS-CoV-2 infection [50,[55][56][57][58].…”
Section: Epidemiology and Presentationmentioning
confidence: 99%
“…O delirium consiste em um distúrbio agudo e flutuante 1-5 da cognição 1 e consciência 1,3 que cursa com desatenção [1][2][3][4][5] , confusão mental [1][2][3]5 ou alteração do nível de consciência 2,5 . Entre as manifestações clínicas estão agitação, delírios, alucinações e distúrbios do ciclo sonovigília 6 .…”
Section: Introductionunclassified
“…Nos pacientes hospitalizados, acredita-se que cerca de 30 a 40% dos casos de delirium ocorrem devido a presença de fatores de risco modificáveis 10. Entre os efeitos adversos proporcionados pelo delirium estão estadia hospitalar prolongada [1][2][3][4]6 , altos custos 3,4 , ventilação mecânica prolongada, declínio cognitivo após alta 4 , aumento de morbidade e mortalidade 1,3,4,6,7 intra e extra-hospitalares 4,7 . Estima-se que, anualmente, nos Estados Unidos, são gastos cerca de 10 bilhões de dólares com custos sociais e de saúde com o delirium 7 .…”
Section: Introductionunclassified